Human genes differ by their UV sensitivity estimated through analysis of UV‐induced silent mutations in melanoma. Issue 10 (15th July 2020) - Gorlov, Ivan P.; Amos, Christopher I.; Tsavachidis, Spiridon; Begg, Colin; Hernando, Eva; Cheng, Chao; Shen, Ronglai; Orlow, Irene; Luo, Li; Ernstoff, Marc S.; Parker, Joel; Thomas, Nancy E.; et al.
Abstract: We hypothesized that human genes differ by their sensitivity to ultraviolet (UV) exposure. We used somatic mutations detected by genome‐wide screens in melanoma and reported in the Catalog Of Somatic Mutations In Cancer. As a measure of UV sensitivity, we used the number of silent mutations generated by C>T transitions in pyrimidine dimers of a given transcript divided by the number of potential sites for this type of mutations in the transcript. We found that human genes varied by UV sensitivity by two orders of magnitude. We noted that the melanoma‐associated tumor suppressor gene CDKN2A was among the top five most UV‐sensitive genes in the human genome. Melanoma driver genes have a higher UV‐sensitivity compared with other genes in the human genome. The difference was more prominent for tumor suppressors compared with oncogene. The results of this study suggest that differential sensitivity of human transcripts to UV light may explain melanoma specificity of some driver genes. Practical significance of the study relates to the fact that differences in UV sensitivity among human genes need to be taken into consideration whereas predicting melanoma‐associated genes by the number of somatic mutations detected in a given gene. Abstract :